Innovation in Preserving and Conserving Book Heritage - Batori, Armida (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
The Istituto Centrale di Patologia del Libro (ICPL) is a branch of the Italian Ministry of Cultural Heritage and Activities whose work is chiefly concerned with research and specialized training in the conservation and restoration of library materials. The Institute was founded in 1938 during a truly propitious period for cultural heritage in general. It was in 1939, in fact, that Law No. 1089 - ’The Safeguarding of Articles of Artistic and Historic Interest’ - was issued, and in the same year the Istituto Centrale di Restauro was established under the direction of Cesare Brandi.